Regulation of Foxp3+ inducible regulatory T cell stability by SOCS2. - FALLON, PADRAIC (My University, 2013)
Suppressor of cytokine signaling (SOCS) proteins are key regulators of CD4+ T cell differentiation, and in particular, we have recently shown that SOCS2 inhibits the development of Th2 cells and allergic immune responses. Interestingly, transcriptome analyses have identified SOCS2 as being preferentially expressed in both natural regulatory T cells (Tregs) and inducible Tregs (iTregs); however, the role of SOCS2 in Foxp3+ Treg function or development has not been fully elucidated. In this study, we show that despite having no effect on natural Treg development or function, SOCS2 is highly expressed in iTregs and required for the stable expression of Foxp3 in iTregs in vitro and in vivo. Indeed, SOCS2-deficient CD4+ T cells upregulated Foxp3 following in vitro TGF-β stimulation, but failed to maintain stable expression of Foxp3. Moreover, in vivo generation of iTregs following OVA feeding was impaired in the absence of SOCS2 and could be rescued in the presence of IL-4 neutralizing Ab. Following IL-4 stimulation, SOCS2-deficient Foxp3+ iTregs secreted elevated IFN-γ and IL-13 levels and displayed enhanced STAT6 phosphorylation. Therefore, we propose that SOCS2 regulates iTreg stability by downregulating IL-4 signaling. Moreover, SOCS2 is essential to maintain the anti-inflammatory phenotype of iTregs by preventing the secretion of proinflammatory cytokines. Collectively, these results suggest that SOCS2 may prevent IL-4–induced Foxp3+ iTreg instability. Foxp3+ iTregs are key regulators of immune responses at mucosal surfaces; therefore, this dual role of SOCS2 in both Th2 and Foxp3+ iTregs reinforces SOCS2 as a potential therapeutic target for Th2-biased diseases.
PUBLISHED
Keywords: T-cells; Immunology, Inflammation & Infection; Biomedical sciences